Draft genome sequence data of a clinical Enterococcus faecalis isolate SHH039 from a patient with cholecystitis from a tertiary care hospital in Sabah, Malaysia - Nur Nashyiroh Izayati Mastor; Vijay Kumar Subbiah; Wan Nazirah Wan Abu Bakar; Khurshida Begum; M. Jahangir Alam; Mohammad Zahirul Hoque (Elsevier Inc., 2022)
An Enterococcus faecalis strain SHH039 was isolated from a 68 year old man who was hospitalised with cholecystitis. The genomic sequence of this isolate which had a size of 2,990,081 bp and 2,663 proteins with functional assignments is presented here. Analysis of the genome revealed Enterococ- cus faecalis with multiple antibiotic resistance genes which may be associated with acute cholecystitis. It may be not clear if the infection symptoms are the consequence of ente- rococci manifestation. However, this opportunistic organism may play a minor role in the disease.